Pengaruh Pengelolaan Alokasi Dana Desa, Kebijakan Desa dan Partisipasi Masyarakat Terhadap Pembangunan Desa Giriwarno - Rini Handayani; Suprihati Suprihati; Wikan Budi Utami (Jurnal Akuntansi dan Pajak, 2024)
This study aims to examine and analyze the Influence of Allocation Management, Village Policy and Community Participation on the Development of Giriwarno Village. This research uses a quantitative descriptive approach. The technique used is primary data by means of a questionnaire distributed to respondents called a questionnaire. The data collection technique uses proportional sampling, namely the technique of determining the sample by knowing in advance the type of age or category in the population, and we will take a sample of 98 samples in this study. Based on these conclusions, Management of Village Fund Allocation has a significant positive effect on village development, while Village Policy has a significant positive effect on village development and Community Participation has a positive effect on village development. The results of further research show that Management of Village Fund Allocation, Village Policy and Community Participation jointly have a significant effect on the development of the village of Giriwarno, this is evidenced by the Multiple Linear Regression Analysis Test, F Test, t Test and Determination Test with the SPSS 23 program.